Criminalization and Punishment of Domestic Violence in Egyptian Law (a Comparative Analytical Study) - El-Tohamy, Hala Ahmed Sabry (Journal of Legal and Political Studies, 2018)
This study deals with the criminalization and punishment of domestic violence in the Egyptian and comparative penal law as part of the increasing trend in criminal legislation in many countries and autonomous regions in the region, including, the Kurdistan Region of Iraq. This paper presents an introduction, two chapters and a conclusion. The introduction deals with the issue of domestic violence through some international and Egyptian statistics on family violence, its importance, scope, methodology and plan. The first topic deals with the nature of family violence, in terms of definition, types, causes and effects. Family violence refers to the mistreatment of someone else who has a close relationship, such as the relationship between husband and wife, between parents and children, between brothers, and between relatives in general. The second topic dealt with the criminalization of domestic violence and punishment in Egyptian law, compared to some Arab legislation, such as Iraqi law and legislation in the Kurdistan region, where the researcher dealt with the first demand criminalization of violence against women and punishment, and focused on research on certain types of domestic violence, Against women, such as FGM / C, and how the Egyptian legislator faced a sanctions report on who was participating in or participating in it. The second requirement was to discuss domestic violence against children in terms of criminalization and punishment in Egyptian legislation, whether in the general penal code or in the Egyptian Child Law, compared with some Arab and foreign legislation. The conclusion of the research includes a set of conclusions and recommendations reached by the researcher, and relates to the adequacy of the legislative organization to achieve public and private deterrence in the field of domestic violence. and the need to establish mechanisms for complaints and communications related to domestic violence by allocating a special police and specialized public prosecution for this purpose, and the importance of issuing a law to combat domestic violence as contained in some positive legislations, the need to establish a court competent in cases against domestic violence, of violence and protect them after reporting the crime.
Keywords: domestic violence; Egyptian statistics; mistreatment; family violence